A Qualitative Exploration of Electronic Image Sharing Among Young People: Navigating the Issues of Conformity, Trust, Intention, and Reputation. (December 2019) - Monks, Helen; Barnes, Amy; Cross, Donna; McKee, Heather
This research sought to explore the main factors affecting young people's image-sharing behaviors, particularly in the context of peer relationships and norms. Ten focus groups were held with young people aged 13 to 14 years (Grade 9) with a total of 68 participants (39 females and 29 males) across 15 Australian schools contributing to the discussions. Focus groups were divided into either all-girls ( n = 4), all-boys ( n = 4), or mixed gender ( n = 2) participants to observe gender-specific issues. Thematic analysis of the data revealed the considerable complexities that young people encounter daily when sharing images in the online environment, including how they navigate issues of conformity, trust, intention, and reputation. Gender-specific differences in young people's perceptions of risky image sharing were also observed. These findings have important implications for the design of school-based interventions to prevent and reduce harm from image-sharing behaviors, including the appointment and training of cyber ambassadors in schools to help positively influence peer-level norms about image sharing.